Eksperimentasi Kreatif Media Pembelajaran Interaktif Berbasis Blended Learning pada Pembelajaran Tematik Sekolah Dasar - Ardian Arief; Hanif Yuda Pratama (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
One of the difficulties for students in understanding the material presented in online is abstract learning. Interactive learning media has advantages, including flexible media that is not limited by space and time, and users can operate according to their needs to solve abstract learning problems. This article describes (1) the process of developing interactive learning media based on blended learning learning theme 8 sub-theme 1 class V SD Negeri Playen III and (2) knowing the feasibility of developing interactive learning media based on blended learning learning theme 8 sub-theme 1 class V SD Negeri Playen III. The design of this article is a design and development research article. This article is carried out with a modified analysis, design, development, implementation, evaluation (ADDIE) development procedure until the implementation stage. The population of this article is the fifth grade students of SD Negeri Playen III. Then samples were taken from the fifth grade teacher and 10 students from 15 students. Data collection techniques using questionnaires, interviews, observations, and documentation. The scores obtained from material experts get an average of 3.75 which is included in the "very good" criteria. The media validation obtained an average of 3.80 which is included in the "very good" criteria. In addition, validation from product user experts (class V teachers) obtained an average of 3.70 which is included in the "very good" criteria. The feasibility of learning media is supported by the student response questionnaire scores conducted at the product trial stage. Based on the results of the student response is 83.67% with the criteria of "very good". The score indicates that blended learning-based interactive learning media is feasible to use.